Non-invasive method for delivery of tracer substances or small quantities of other materials to the colon. Issue 1 (January 1990) - Chacko, A; Szaz, K F; Howard, J; Cummings, J H
Abstract : A miniature osmotic pump has been developed (Osmet) with ALZA, Palo Alto, USA, which can be swallowed, will pass through the stomach and small intestine and then deliver its contents (240 microliters) over eight hours in the large bowel. In vitro studies showed the pumps started to discharge after four to five hours and emptied at a reasonably constant rate of 20.4 microliters/h from 9-16 h (9.6%/h). In vivo studies using gamma-scintigraphy in seven healthy subjects show that the pumps left the fasting stomach at 1.2 h (range 0-3) and arrived in the caecum by 6.4 h (range 5-9). Mean start-up time was 5.3 (0.2) h and the rate of discharge was 15.9 microliters/h for pumps studied from 6-12 h and 17.2 microliters/h for those studied from 10-20 h. This device is simple, safe and effective for the delivery of tracer substances to the caecum and colon without interfering with patients' normal lifestyle.